Kinematics, turbulence, and star formation of z ∼ 1 strongly lensed galaxies seen with MUSE. Issue 1 (3rd March 2018) - Patrício, V; Richard, J; Carton, D; Contini, T; Epinat, B; Brinchmann, J; Schmidt, K B; Krajnović, D; Bouché, N; Weilbacher, P M; Pelló, R; Caruana, J; et al.
Abstract: We analyse a sample of eight highly magnified galaxies at redshift 0.6 < z < 1.5 observed with MUSE, exploring the resolved properties of these galaxies at sub-kiloparsec scales. Combining multiband HST photometry and MUSE spectra, we derive the stellar mass, global star formation rates (SFRs), extinction and metallicity from multiple nebular lines, concluding that our sample is representative of z ∼ 1 star-forming galaxies. We derive the 2D kinematics of these galaxies from the [O ii ] emission and model it with a new method that accounts for lensing effects and fits multiple images simultaneously. We use these models to calculate the 2D beam-smearing correction and derive intrinsic velocity dispersion maps. We find them to be fairly homogeneous, with relatively constant velocity dispersions between 15 and 80 km s −1 and Gini coefficient of 0.3 . We do not find any evidence for higher (or lower) velocity dispersions at the positions of bright star-forming clumps. We derive resolved maps of dust attenuation and attenuation-corrected SFRs from emission lines for two objects in the sample. We use this information to study the relation between resolved SFR and velocity dispersion. We find that these quantities are not correlated, and the high-velocity dispersions found for relatively low star-forming densities seems to indicate that, at sub-kiloparsec scales, turbulence in high- z discs is mainly dominated by gravitational instability rather than stellar feedback.